High-adhesion quick-dry ultraviolet curing ink and preparation method thereof
By using a combination of acrylic modified resin, composite nanofiller and specific photoinitiator, the problems of insufficient adhesion and slow curing speed of UV curing ink are solved, and the effects of high adhesion and quick drying are achieved.
Patent Information
- Application Number
- CN202510178792.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-29
AI Technical Summary
The existing ultraviolet curing inks are insufficient adhesion during the curing process, resulting in the cured film being easily damaged and the curing speed is slow.
The curing activity and adhesion of the ink are improved through specific preparation methods and combination ratios.
High adhesion and quick-drying effects are achieved, and the cured film shows high adhesion and damage resistance on tinplate, wooden boards and glass.
Smart Images

Figure CN119899554A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of novel ink preparation, and in particular relates to a high-adhesion quick-drying ultraviolet light curing ink and a preparation method thereof. Background Art
[0002] UV curing is a process that uses ultraviolet light to trigger a photochemical reaction to generate a cross-linked network of polymers. The principle is as follows: When exposed to UV light, the photoinitiator will undergo a chemical reaction to bond independent oligomers and monomers into more complex chains (also called polymers). This bonding process is called photopolymerization. Through this photopolymerization reaction, objects and materials can be dried and bonded. The following processes are involved: Photoinitiator stage: the photoinitiator absorbs photon energy and is activated under ultraviolet light, and the outer electrons of its molecules undergo transitions to form active electron-hole pairs; generation of free radicals or ions: these active electron-hole pairs can excite the surrounding molecules into free radicals or ions, such as oxygen free radicals, carbon cations, etc.; polymerization, grafting, and cross-linking reactions: these free radicals or ions then interact with the unsaturated groups in the resin to initiate or promote the breaking of the double bonds of the resin, achieve continuous polymerization reactions, and grafting and cross-linking between resins, and finally form a solid film; chain growth and termination: in the polymerization process initiated by these free radicals or ions, the system will undergo further cross-linking and solidify into a film over time. At the same time, free radicals can complete chain termination through coupling or disproportionation.
[0003] Ultraviolet curing ink, also known as UV ink, is an ink that cures under ultraviolet light, usually composed of resin, photosensitizer and additives. According to the curing method, UV curing ink can be divided into free radical curing type and cationic curing type. The difference between the two is whether the photosensitizer generates free radicals or cations after being irradiated by ultraviolet light. According to the application field, UV curing ink can be divided into printing ink, electronic product manufacturing ink, decorative ink, etc. Summary of the invention
[0004] Based on the above problems, the present invention provides a high-adhesion quick-drying UV-curable ink, comprising acrylic modified resin, composite nanofiller, photoinitiator I, photoinitiator II, etc. Diphenylmethane 4,4′-diisocyanate and 2-hydroxypropyl acrylate are used as reactants to prepare substance 1, polylactic acid and maleic anhydride are reacted to obtain substance 2, substance 1 is modified by substance 2, that is, a new type of acrylic modified resin material is obtained, microcrystalline cellulose is modified by 2-ethylhexyl isocyanate to obtain a composite nanofiller, zinc oxide is modified by hexamethylene diisocyanate to obtain photoinitiator I, combined with 2-isopropylthioxanthone, hydroxyethyl methacrylate and diethylene glycol diacrylate of phthalate, the obtained UV-curable ink has a low volume shrinkage, which means that the cured film has a high adhesion. After being actually applied to tinplate, wood board and glass, the film has good adhesion and is not easy to be damaged by naked eye observation, and more active groups mean that it has a high curing activity, thereby achieving quick drying.
[0005] The invention provides a high-adhesion quick-drying ultraviolet curing ink, comprising the following raw materials in parts by mass: 30-50 parts of acrylic modified resin, 3-5 parts of composite nano fillers, 1-3 parts of photoinitiator I, 1-2 parts of photoinitiator II, 5-8 parts of hydroxyethyl methacrylate, and 6-10 parts of diethylene glycol phthalate diacrylate.
[0006] The preparation method of the acrylic acid modified resin is as follows:
[0007] L1. Weigh diphenylmethane 4,4′-diisocyanate, 2-hydroxypropyl acrylate, 4-methoxyphenol and dibutyltin dilaurate in a mass ratio of 25g:0.05g:0.1g, mix diphenylmethane 4,4′-diisocyanate, 4-methoxyphenol and dibutyltin dilaurate under a nitrogen atmosphere, heat to 30-40°C in an oil bath, stir at a speed of 200-250rpm for 10-15min, drop 2-hydroxypropyl acrylate into it, continue the reaction for 5-8h, and then dry in vacuum to obtain substance 1;
[0008] L2. Weigh polylactic acid, maleic anhydride and tin oxide according to the mass ratio of 0.5-0.6g:9.8g:0.05g, stir the polylactic acid at 150°C and 0.01MPa at a speed of 200-300rpm for 2-3h, then add maleic anhydride and tin oxide, adjust the pressure to 8-10kPa, continue stirring and react for 4-5h, and precipitate with deionized water after the reaction. Dry the precipitate at 70-80°C to obtain substance 2;
[0009] L3. Weigh the substance 1 obtained in step L1 and the substance 2 obtained in step L2 in a molar ratio of 1:1, add 2,6-di-tert-butyl-p-cresol, heat to 70-80°C in an oil bath, and stir at a speed of 200-300 rpm for 1-2 hours to obtain a mixture 1, add anhydrous ethanol to the mixture 1, and stir at a speed of 100-150 rpm for 15-20 minutes. After the stirring, precipitate with deionized water, and obtain an acrylic acid modified resin after vacuum drying.
[0010] Preferably, in step L1, the CAS number of diphenylmethane 4,4′-diisocyanate is 101-68-8, the CAS number of 2-hydroxypropyl acrylate is 999-61-1, the CAS number of 4-methoxyphenol is 150-76-5, and the CAS number of dibutyltin dilaurate is 77-58-7.
[0011] Preferably, the CAS number of the polylactic acid in step L2 is 26023-30-3, the polylactic acid preferably has a molecular weight of 20,000-30,000, the CAS number of maleic anhydride is 108-31-6, and the CAS number of tin oxide is 21651-19-4.
[0012] Preferably, in step L3, the CAS number of 2,6-di-tert-butyl-p-cresol is 128-37-0, the amount of 2,6-di-tert-butyl-p-cresol added is 5%-10% of the mass of substance 2, and the amount of anhydrous ethanol added is 20-30% of the mass of mixture 1.
[0013] The preparation method of the composite nanofiller is as follows:
[0014] S1. Weigh microcrystalline cellulose, dimethyl sulfoxide, 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate according to the mass volume ratio of 1g:30-50mL:1-2g:0.002-0.004g:0.005-0.008g, ultrasonically treat the microcrystalline cellulose and dimethyl sulfoxide at a power of 250-300W for 1-2h, heat the oil bath to 50-60°C after the treatment, add 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate, and stir at a speed of 100-200rpm for 18-20h to obtain a mixture 2;
[0015] S2. The mixture 2 obtained in step S1 is washed 3-5 times with tetrahydrofuran, centrifuged at 8000-10000g for 20-30min, and the obtained precipitate is dispersed in dibutyltin dilaurate, and the mass percentage concentration of the precipitate in dibutyltin dilaurate is 3-5%, so as to obtain a composite nanofiller.
[0016] Preferably, the CAS number of the microcrystalline cellulose in step S1 is 9004-34-6, and the CAS number of 2-ethylhexyl isocyanate is 20392-34-1.
[0017] The preparation method of the photoinitiator I is as follows:
[0018] V1. Weigh zinc oxide, toluene, dibutyltin dilaurate, and hexamethylene diisocyanate in a mass ratio of 16.2 g: 80-100 g: 0.05-0.08 g: 16.8 g, place zinc oxide in toluene, heat to 40-50° C., and perform ultrasonic treatment at a power of 180-240 W for 1-2 h to obtain a mixture 3;
[0019] V2. Under a nitrogen atmosphere, dibutyltin dilaurate and hexamethylene diisocyanate are mixed evenly, and then dropped into the mixture 3 obtained in step V1, heated to 60-70°C, stirred at a speed of 180-200rpm for 3-4h, and then centrifuged at a centrifugal force of 7000-8000g for 30-45min. The obtained precipitate is washed with anhydrous ethanol and vacuum dried to obtain photoinitiator I.
[0020] Preferably, the CAS number of hexamethylene diisocyanate in step V1 is 822-06-0.
[0021] The photoinitiator II is 2-isopropylthioxanthone, the CAS number of 2-isopropylthioxanthone is 5495-84-1, the CAS number of hydroxyethyl methacrylate is 868-77-9, and the CAS number of diethylene glycol phthalate diacrylate is 42978-66-5.
[0022] The present invention also provides a method for preparing a high-adhesion quick-drying ultraviolet curing ink, the specific steps of which are as follows:
[0023] The raw materials are weighed respectively by weight and mixed evenly to obtain a high-adhesion quick-drying UV curing ink.
[0024] The beneficial effects of the present invention are as follows:
[0025] The invention prepares a high-adhesion quick-drying ultraviolet curing ink, which comprises an acrylic acid modified resin, a composite nanofiller, a photoinitiator I, a photoinitiator II, etc., wherein the structure of the acrylic acid modified resin is as follows: Figure 1As shown, diphenylmethane 4,4′-diisocyanate and 2-hydroxypropyl acrylate are used as reactants to prepare substance 1, polylactic acid and maleic anhydride react to obtain substance 2, and substance 1 is modified by substance 2 to obtain a new type of acrylic modified resin material, which is better than the traditional polyurethane acrylate resin material, has a higher functionality, that is, more reaction sites, and thus has a faster crosslinking reaction rate and achieves quick drying. The composite nanofiller is obtained by modifying microcrystalline cellulose, and its structure is as follows Figure 2 As shown in Figure 1, 2-ethylhexyl isocyanate is connected to microcrystalline cellulose, and the obtained composite nanofiller can be evenly dispersed in acrylic modified resin with more reactive groups, thereby improving surface hardness and mechanical properties. Photoinitiator I is obtained by modifying inorganic material zinc oxide with hexamethylene diisocyanate. Zinc oxide has double bonds that participate in ultraviolet light curing reaction. The modified photoinitiator I further promotes curing. When it works together with photoinitiator II, its initiation effect is stronger than that of a single photoinitiator. In addition, hydroxyethyl methacrylate and diethylene glycol diacrylate of phthalate can be used as active diluents to adjust the viscosity of ink.
[0026] The ultraviolet light-curing ink obtained by the present invention has a lower volume shrinkage rate, which means that the cured film has higher adhesion. After being actually applied to tinplate, wood board and glass, the film has better adhesion and is not easy to be damaged when observed with the naked eye. More active groups mean that it has higher curing activity, thereby achieving quick drying. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 Schematic diagram of the structure of acrylic acid modified resin;
[0029] Figure 2 Schematic diagram of the structure of the precipitate during the preparation of composite nanofillers. DETAILED DESCRIPTION
[0030] In order to more clearly explain the overall concept of the present application, the following is described in detail in conjunction with the accompanying drawings of the specification by way of embodiment. In the following description, a large number of specific details are provided to provide a more thorough understanding of the present invention. However, it is obvious to those skilled in the art that the present invention can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present invention, some technical features well known in the art are not described.
[0031] Embodiment 1: This embodiment provides a method for preparing an acrylic acid modified resin, and the specific steps are as follows:
[0032] L1. Weigh diphenylmethane 4,4′-diisocyanate, 2-hydroxypropyl acrylate, 4-methoxyphenol and dibutyltin dilaurate in a mass ratio of 25g:0.05g:0.1g, mix diphenylmethane 4,4′-diisocyanate, 4-methoxyphenol and dibutyltin dilaurate under a nitrogen atmosphere, heat to 30°C in an oil bath, stir at 200 rpm for 10 min, drop 2-hydroxypropyl acrylate into the mixture, continue the reaction for 5 h, and then dry in vacuum to obtain substance 1;
[0033] L2. Polylactic acid, maleic anhydride and tin oxide were weighed in a mass ratio of 0.5g:9.8g:0.05g, with the polylactic acid having a molecular weight of 20,000. The polylactic acid was stirred at 150°C and 0.01MPa at a speed of 200rpm for 2h, and then maleic anhydride and tin oxide were added, the pressure was adjusted to 8kPa, and the stirring reaction was continued for 4h. After the reaction, deionized water was used for precipitation, and the obtained precipitate was dried at 70°C to obtain substance 2;
[0034] L3. Weigh the substance 1 obtained in step L1 and the substance 2 obtained in step L2 in a molar ratio of 1:1, add 2,6-di-tert-butyl-p-cresol in an amount of 5% of the mass of substance 2, heat in an oil bath to 70°C, and stir at 200 rpm for 1 hour to obtain a mixture 1, add anhydrous ethanol to the mixture 1 in an amount of 20% of the mass of the mixture 1, stir at 100 rpm for 15 minutes, precipitate with deionized water, and obtain an acrylic acid modified resin after vacuum drying.
[0035] Embodiment 2: This embodiment provides a method for preparing an acrylic acid modified resin, and the specific steps are as follows:
[0036] L1. Weigh diphenylmethane 4,4′-diisocyanate, 2-hydroxypropyl acrylate, 4-methoxyphenol and dibutyltin dilaurate in a mass ratio of 25g:0.05g:0.1g, mix diphenylmethane 4,4′-diisocyanate, 4-methoxyphenol and dibutyltin dilaurate under a nitrogen atmosphere, heat to 35°C in an oil bath, stir at 220rpm for 12min, drop 2-hydroxypropyl acrylate into the mixture, continue the reaction for 6h, and then dry under vacuum to obtain substance 1;
[0037] L2. Weigh polylactic acid, maleic anhydride and tin oxide according to the mass ratio of 0.5g:9.8g:0.05g, where polylactic acid has a molecular weight of 24,000. Stir the polylactic acid at 150°C and 0.01MPa at a speed of 250rpm for 2.5h, then add maleic anhydride and tin oxide, adjust the pressure to 9kPa, continue stirring and react for 4.5h, and after the reaction, precipitate with deionized water. Dry the precipitate at 75°C to obtain substance 2;
[0038] L3. Weigh the substance 1 obtained in step L1 and the substance 2 obtained in step L2 at a molar ratio of 1:1, add 2,6-di-tert-butyl-p-cresol in an amount of 8% of the mass of substance 2, heat in an oil bath to 75°C, and stir at a speed of 250 rpm for 1.5 hours to obtain a mixture 1, add anhydrous ethanol to the mixture 1 in an amount of 25% of the mass of the mixture 1, stir at a speed of 120 rpm for 18 minutes, precipitate with deionized water after the end, and obtain an acrylic acid modified resin after vacuum drying.
[0039] Embodiment 3: This embodiment provides a method for preparing an acrylic acid modified resin, and the specific steps are as follows:
[0040] L1. Weigh diphenylmethane 4,4′-diisocyanate, 2-hydroxypropyl acrylate, 4-methoxyphenol and dibutyltin dilaurate in a mass ratio of 25g:0.05g:0.1g, mix diphenylmethane 4,4′-diisocyanate, 4-methoxyphenol and dibutyltin dilaurate under a nitrogen atmosphere, heat to 40°C in an oil bath, stir at 250rpm for 15min, drop 2-hydroxypropyl acrylate into the mixture, continue the reaction for 8h, and then dry in vacuum to obtain substance 1;
[0041] L2. Polylactic acid, maleic anhydride and tin oxide were weighed in a mass ratio of 0.5g:9.8g:0.05g, with the polylactic acid having a molecular weight of 30,000. The polylactic acid was stirred at 150°C and 0.01MPa at a speed of 300rpm for 3h, and then maleic anhydride and tin oxide were added, the pressure was adjusted to 10kPa, and the stirring reaction was continued for 5h. After the reaction, deionized water was used for precipitation, and the obtained precipitate was dried at 80°C to obtain substance 2;
[0042] L3. Weigh the substance 1 obtained in step L1 and the substance 2 obtained in step L2 in a molar ratio of 1:1, add 2,6-di-tert-butyl-p-cresol in an amount of 10% of the mass of substance 2, heat to 80°C in an oil bath, and stir at 300 rpm for 2 hours to obtain a mixture 1, add anhydrous ethanol to the mixture 1 in an amount of 30% of the mass of the mixture 1, stir at 150 rpm for 20 minutes, precipitate with deionized water, and obtain an acrylic acid modified resin after vacuum drying.
[0043] Embodiment 4: This embodiment provides a method for preparing a composite nanofiller, and the specific steps are as follows:
[0044] S1. Weigh microcrystalline cellulose, dimethyl sulfoxide, 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate according to the mass volume ratio of 1g:30mL:1g:0.002g:0.005g, ultrasonically treat the microcrystalline cellulose and dimethyl sulfoxide at a power of 250W for 1h, heat the oil bath to 50°C after the ultrasonic treatment, add 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate, and stir at a speed of 100rpm for 18h to obtain a mixture 2;
[0045] S2. The mixture 2 obtained in step S1 is washed three times with tetrahydrofuran, centrifuged at 8000g for 20 minutes, and the obtained precipitate is dispersed in dibutyltin dilaurate, and the mass percentage concentration of the precipitate in dibutyltin dilaurate is 3%, thereby obtaining a composite nanofiller.
[0046] Embodiment 5: This embodiment provides a method for preparing a composite nanofiller, and the specific steps are as follows:
[0047] S1. Weigh microcrystalline cellulose, dimethyl sulfoxide, 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate according to the mass volume ratio of 1g:40mL:1.5g:0.003g:0.006g, ultrasonically treat microcrystalline cellulose and dimethyl sulfoxide at a power of 280W for 1.5h, heat the oil bath to 55°C after the treatment, add 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate, and stir at a speed of 150rpm for 19h to obtain mixture 2;
[0048] S2. The mixture 2 obtained in step S1 is washed 4 times with tetrahydrofuran, centrifuged at 9000g for 25 minutes, and the obtained precipitate is dispersed in dibutyltin dilaurate, and the mass percentage concentration of the precipitate in dibutyltin dilaurate is 4%, thereby obtaining a composite nanofiller.
[0049] Embodiment 6: This embodiment provides a method for preparing a composite nanofiller, and the specific steps are as follows:
[0050] S1. Weigh microcrystalline cellulose, dimethyl sulfoxide, 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate according to the mass volume ratio of 1g:50mL:2g:0.004g:0.008g, treat microcrystalline cellulose and dimethyl sulfoxide with ultrasound at 300W for 2h, heat the oil bath to 60°C after the treatment, add 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate, and stir at 200rpm for 20h to obtain mixture 2;
[0051] S2. The mixture 2 obtained in step S1 is washed 4 times with tetrahydrofuran, centrifuged at 10000g centrifugal force for 30min, and the obtained precipitate is dispersed in dibutyltin dilaurate, and the mass percentage concentration of the precipitate in dibutyltin dilaurate is 5%, so as to obtain a composite nanofiller.
[0052] Embodiment 7: This embodiment provides a method for preparing photoinitiator I, and the specific steps are as follows:
[0053] V1. Weigh zinc oxide, toluene, dibutyltin dilaurate, and hexamethylene diisocyanate in a mass ratio of 16.2 g: 80 g: 0.05 g: 16.8 g, place zinc oxide in toluene, heat to 40° C., and perform ultrasonic treatment at a power of 180 W for 1 h, to obtain a mixture 3;
[0054] V2. Under a nitrogen atmosphere, dibutyltin dilaurate and hexamethylene diisocyanate were mixed evenly, and then dropped into the mixture 3 obtained in step V1, heated to 60°C, stirred at a speed of 180 rpm for 3 hours, and then centrifuged at a centrifugal force of 7000g for 30 minutes. The obtained precipitate was washed with anhydrous ethanol and vacuum dried to obtain photoinitiator I.
[0055] Embodiment 8: This embodiment provides a method for preparing photoinitiator I, and the specific steps are as follows:
[0056] V1. Weigh zinc oxide, toluene, dibutyltin dilaurate, and hexamethylene diisocyanate in a mass ratio of 16.2 g: 90 g: 0.06 g: 16.8 g, place zinc oxide in toluene, heat to 45° C., and ultrasonically treat at a power of 200 W for 1.5 h to obtain a mixture 3;
[0057] V2. Under a nitrogen atmosphere, dibutyltin dilaurate and hexamethylene diisocyanate were mixed evenly, and then dropped into the mixture 3 obtained in step V1, heated to 65°C, stirred at a speed of 190 rpm for 3.5 hours, and then centrifuged at a centrifugal force of 7500g for 38 minutes. The obtained precipitate was washed with anhydrous ethanol and vacuum dried to obtain photoinitiator I.
[0058] Embodiment 9: This embodiment provides a method for preparing photoinitiator I, and the specific steps are as follows:
[0059] V1. Weigh zinc oxide, toluene, dibutyltin dilaurate, and hexamethylene diisocyanate in a mass ratio of 16.2 g: 100 g: 0.08 g: 16.8 g, place zinc oxide in toluene, heat to 50° C., and ultrasonically treat at 240 W for 2 h to obtain a mixture 3;
[0060] V2. Under a nitrogen atmosphere, dibutyltin dilaurate and hexamethylene diisocyanate were mixed evenly, and then dropped into the mixture 3 obtained in step V1, heated to 70°C, stirred at 200 rpm for 4 hours, and then centrifuged at 8000g for 45 minutes. The obtained precipitate was washed with anhydrous ethanol and vacuum dried to obtain photoinitiator I.
[0061] Embodiment 10: This embodiment provides a method for preparing a high-adhesion quick-drying UV-curable ink, the specific contents of which are as follows:
[0062] The raw materials are weighed according to the following mass proportions: 30 parts of acrylic modified resin, 3 parts of composite nanofiller, 1 part of photoinitiator I, 1 part of photoinitiator II, 5 parts of hydroxyethyl methacrylate, and 6 parts of diethylene glycol diacrylate phthalate, wherein the acrylic modified resin is prepared by Example 1, the composite nanofiller is prepared by Example 4, the photoinitiator I is prepared by Example 7, and the photoinitiator II is 2-isopropylthioxanthone. After the above raw materials are evenly mixed, the high-adhesion quick-drying UV-curable ink of this example is obtained.
[0063] Embodiment 11: This embodiment provides a method for preparing a high-adhesion quick-drying UV-curable ink, the specific contents of which are as follows:
[0064] The raw materials are weighed according to the following mass proportions: 40 parts of acrylic modified resin, 4 parts of composite nanofiller, 2 parts of photoinitiator I, 1.5 parts of photoinitiator II, 6 parts of hydroxyethyl methacrylate, and 8 parts of diethylene glycol diacrylate phthalate, wherein the acrylic modified resin is prepared by Example 2, the composite nanofiller is prepared by Example 5, the photoinitiator I is prepared by Example 8, and the photoinitiator II is 2-isopropylthioxanthone. After the above raw materials are evenly mixed, the high-adhesion quick-drying UV-curable ink of this example is obtained.
[0065] Embodiment 12: This embodiment provides a method for preparing a high-adhesion quick-drying UV-curable ink, the specific contents of which are as follows:
[0066] The raw materials are weighed according to the following mass proportions: 50 parts of acrylic modified resin, 5 parts of composite nanofiller, 3 parts of photoinitiator I, 2 parts of photoinitiator II, 8 parts of hydroxyethyl methacrylate, and 10 parts of diethylene glycol diacrylate phthalate, wherein the acrylic modified resin is prepared by Example 3, the composite nanofiller is prepared by Example 6, the photoinitiator I is prepared by Example 9, and the photoinitiator II is 2-isopropylthioxanthone. After the above raw materials are evenly mixed, the high-adhesion quick-drying UV-curable ink of this embodiment is obtained.
[0067] Comparative Example 1: This comparative example provides a method for preparing a UV-curable ink, and the specific contents are as follows:
[0068] The UV-curable ink of this comparative example is different from Example 10 in that polyurethane acrylate is used to replace the acrylic modified resin. The polyurethane acrylate is purchased from Wuhan Kamik Co., Ltd. The other steps are consistent with Example 10 to obtain the UV-curable ink of this comparative example.
[0069] Comparative Example 2: This comparative example provides a method for preparing a UV-curable ink, the specific contents of which are as follows:
[0070] The UV-curable ink of this comparative example is different from Example 10 in that microcrystalline cellulose is used instead of the composite nanofiller, and the other steps are consistent with Example 10 to obtain the UV-curable ink of this comparative example.
[0071] Comparative Example 3: This comparative example provides a method for preparing a UV-curable ink, the specific contents of which are as follows:
[0072] The UV-curable ink of this comparative example is different from Example 10 in that zinc oxide is used to replace photoinitiator I and photoinitiator II, and the other steps are consistent with Example 10 to obtain the UV-curable ink of this comparative example.
[0073] Comparative Example 4: This comparative example provides a method for preparing a UV-curable ink, and the specific contents are as follows:
[0074] The UV-curable ink of this comparative example is different from that of Example 10 in that it does not contain photoinitiator I, and the other steps are consistent with those of Example 10 to obtain the UV-curable ink of this comparative example.
[0075] Experimental test-ink performance test method:
[0076] The UV-curable inks obtained in Examples 10-12 and Comparative Examples 1-4 were tested.
[0077] 1. Adhesion test:
[0078] Adhesion was measured using the American Society for Testing and Materials standard ASTM D3359 "Standard Test Method for Evaluating Adhesion Grades by Tape Test". The test substrates were tinplate, wood and glass. They were quickly placed under a light curing machine to cure into a film. 2. Pencil hardness test:
[0079] The pencil hardness test of the coating film was carried out according to the national standard "GB / T6739-2022 Determination of film hardness by pencil method for paint and varnish". A coating film with a thickness of 150mm×100mm×0.05mm was prepared on an ABS board of 150mm×100mm×0.8mm. Pencils of different hardness were placed in the pencil hardness tester respectively, and the angle between the pencil and the ABS board was always kept at 45°. The pencil hardness tester was pushed horizontally to observe the cracking of the coating film.
[0080] 3. Volume shrinkage test:
[0081] The density of the coating before UV curing was measured by volume method (ρ = m0gV0 -1 ), recorded as ρ0, the coating density after UV curing is measured by solid density meter MH-300A, recorded as ρ1. At room temperature, the volume shrinkage rate is calculated as follows:
[0082] Volume shrinkage = (ρ1-ρ0) / ρ0×100%;
[0083] The average of three measurements is the final volume shrinkage.
[0084] 4. Solvent resistance test:
[0085] The solvent resistance of the sample is characterized by its absorption rate of the solvent. At room temperature, weigh an appropriate amount of photocured film sample and immerse it in a sealed glass bottle containing water, anhydrous ethanol and toluene. After immersion for 48 hours, take out the photocured film sample and absorb the excess solvent on the surface of the photocured film with filter paper and weigh it again. Record the mass of the photocured film before immersion, recorded as m0, and the mass of the photocured film dried with filter paper after immersion, recorded as m1, and calculate the absorption rate according to the following formula:
[0086] Absorption rate = m1 / m0×100%.
[0087] 5. Gel rate test:
[0088] At room temperature, weigh an appropriate amount of photocured film sample and immerse it in a sealed glass bottle filled with acetone. After immersion for 48 hours, take out the photocured film sample and place it in a 60℃ vacuum drying oven to dry to constant weight. Record the mass of the photocured film before immersion as m2, and the mass of the photocured film after drying as m3. Calculate the gel fraction according to the following formula:
[0089] Gel content = m3 / m2×100%.
[0090] The experimental results are as follows:
[0091] Table 1 Ink performance test results
[0092]
[0093] The performance test results of the ink are shown in Table 1. It can be seen from Table 1 that the UV-curable inks obtained in Examples 10-12 have a lower volume shrinkage, which means that the cured film has a higher adhesion. After being actually applied to tinplate, wood and glass, the film has good adhesion and is not easy to break when observed with the naked eye. In contrast, the UV-curable inks of Comparative Examples 1-4 performed poorly, especially in terms of volume shrinkage, which was significantly higher than the data of the examples under the same test conditions.
[0094] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the protection scope of the technical solution of the present invention.
Claims
1. A high-adhesion quick-drying UV-curable ink, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of acrylic modified resin, 3-5 parts of composite nano filler, 1-3 parts of photoinitiator I, 1-2 parts of photoinitiator II, 5-8 parts of hydroxyethyl methacrylate and 6-10 parts of diethylene glycol phthalate diacrylate.
2. The high-adhesion quick-drying UV curing ink according to claim 1, characterized in that: The preparation method of the acrylic acid modified resin is as follows: L1. Weigh diphenylmethane 4,4′-diisocyanate, 2-hydroxypropyl acrylate, 4-methoxyphenol and dibutyltin dilaurate in a mass ratio of 25g:0.05g:0.1g, mix diphenylmethane 4,4′-diisocyanate, 4-methoxyphenol and dibutyltin dilaurate under a nitrogen atmosphere, heat in an oil bath, stir, drop 2-hydroxypropyl acrylate into, continue the reaction for 5-8h, and vacuum dry after completion to obtain substance 1; L2. Weigh polylactic acid, maleic anhydride and tin oxide according to the mass ratio of 0.5-0.6g:9.8g:0.05g, stir the polylactic acid at 150°C and 0.01MPa, then add maleic anhydride and tin oxide, adjust the pressure, continue stirring the reaction, precipitate with deionized water after the reaction, dry the precipitate to obtain substance 2; L3. Weigh the substance 1 obtained in step L1 and the substance 2 obtained in step L2 in a molar ratio of 1:1, add 2,6-di-tert-butyl-p-cresol, heat in an oil bath, stir to obtain a mixture 1, add anhydrous ethanol to the mixture 1, stir, precipitate with deionized water after completion, and obtain an acrylic acid modified resin after vacuum drying.
3. The high-adhesion quick-drying UV-curable ink according to claim 2, characterized in that: In step L3, the amount of 2,6-di-tert-butyl-p-cresol added is 5%-10% of the mass of substance 2, and the amount of anhydrous ethanol added is 20-30% of the mass of mixture 1.
4. The high-adhesion quick-drying UV-curable ink according to claim 3, characterized in that: The preparation method of the composite nanofiller is as follows: S1. weigh microcrystalline cellulose, dimethyl sulfoxide, 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate according to the mass volume ratio of 1g:30-50mL:1-2g:0.002-0.004g:0.005-0.008g, ultrasonically treat the microcrystalline cellulose and dimethyl sulfoxide, heat in an oil bath after the ultrasonic treatment, add 2-ethylhexyl isocyanate, 4-methoxyphenol and dibutyltin dilaurate, and stir to obtain a mixture 2; S2. The mixture 2 obtained in step S1 is washed with tetrahydrofuran and centrifuged. The obtained precipitate is dispersed in dibutyltin dilaurate. The mass percentage concentration of the precipitate in dibutyltin dilaurate is 3-5%, and a composite nanofiller is obtained.
5. The high-adhesion quick-drying UV curing ink according to claim 4, characterized in that: The preparation method of the photoinitiator I is as follows: V1. Weigh zinc oxide, toluene, dibutyltin dilaurate, and hexamethylene diisocyanate in a mass ratio of 16.2 g: 80-100 g: 0.05-0.08 g: 16.8 g, place zinc oxide in toluene, heat, and ultrasonically treat to obtain a mixture 3; V2. Under a nitrogen atmosphere, dibutyltin dilaurate and hexamethylene diisocyanate are mixed evenly, and then dropped into the mixture 3 obtained in step V1, heated, stirred, and centrifuged after completion. The obtained precipitate is washed with anhydrous ethanol and vacuum dried to obtain photoinitiator I.
6. The high-adhesion quick-drying UV curing ink according to claim 5, characterized in that: The photoinitiator II is 2-isopropylthioxanthone.
7. A method for preparing the high-adhesion quick-drying UV-curable ink according to claims 1-6, characterized in that: The raw materials are weighed respectively by weight and mixed evenly to obtain a high-adhesion quick-drying UV curing ink.